Re-anchorage of a ruptured tendon in bonded post-tensioned concrete beams: model validation - Abdelatif, Amged O.; Owen, John S.; Hussein, Mohammed F.M. (Trans Tech Publications Inc., 2013)
Many post-tensioned concrete bridges have been reported to have ruptured tendons due to corrosion [1] and the assessment of their residual structural capacity has to account for the possibility of re-anchorage of failed tendons. This paper presents an experimental programme to validate a numerical model developed by the authors for the re-anchorage of a ruptured tendon in post-tensioned concrete [2]. The experimental programme considered 33 post-tensioned concrete prisms, in which the rupture of tendon was simulated by releasing the tendon at one end. The full field displacement at concrete surface after release was measured using 3D Electronic Speckle Pattern Interferometry (ESPI). A wide range of parameters: tendon diameter, duct material, grout strength, concrete strength and shear reinforcement were investigated to validate the proposed model, which is found to be suitable for use in assessing post-tensioned concrete bridges with damaged tendons.